The Implementation of SCL in Teaching Arabic for Islamic Finance: A Dynamic Approach in Preparing For Education 4.0 - Muhsin, Muhammad Anas Al; Ahmad, Nor Zahidah; Sarudin, Anida; Muhammad, Mastura; Othman, Zulkifli; Makki, Saiyid; Kassymova, Gulzhaina K. (International Journal of Psychosocial Rehabilitation, 2020)
The implication of Industrial Revolution 4.0 has sparked education system all over the world. The impact of IR 4.0 driven reformation in the structure and management of higher education. A grand shift of University 1.0 to University 4.0 urges many transformations in producing an omnipresent knowledgeable and talented graduates for a global society and economic demands. In order to cope with these technologies and innovations breakthroughs, education should be aligning with industry requirements in term of approach used, learning strategies, modules, course assessments, job readiness, and etc. This paper will give an overview on the compatibility of practising Student –Centred Learning (SCL) approach in teaching Language for Specific Purposes (LSP), with special reference on Arabic for Islamic finance. It also will explore the Education 4.0 elements in preparing LSP students and teachers facing future challenges in the new 21st century era.